Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.annemergmed.2020.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Therapy and Risk of Infection for Health Care Workers Caring for Patients With Viral Severe Acute Respiratory Infection: A Systematic Review and Meta-analysis

Abstract: Study objective To synthesize the evidence regarding the infection risk associated with different modalities of oxygen therapy used in treating patients with severe acute respiratory infection. Health care workers face significant risk of infection when treating patients with a viral severe acute respiratory infection. To ensure health care worker safety and limit nosocomial transmission of such infection, it is crucial to synthesize the evidence regarding the infection risk associated with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…HCWs are among the groups at the highest risk of both contracting the SARS-CoV-2 virus and developing severe COVID-19. 4 Using healthy subjects, our study suggests that lower flow HFNC, a NRB, CPAP, and patient mask usage can modestly reduce the generation of smaller-sized aerosols. Our study further suggests that aerosol-sized PM may be generated even in healthy subjects, without coughing or increased sputum, because of airway shear stress, vibration, and sporadic collapse/reopening of terminal bronchioles.…”
Section: Limitationsmentioning
confidence: 73%
See 1 more Smart Citation
“…HCWs are among the groups at the highest risk of both contracting the SARS-CoV-2 virus and developing severe COVID-19. 4 Using healthy subjects, our study suggests that lower flow HFNC, a NRB, CPAP, and patient mask usage can modestly reduce the generation of smaller-sized aerosols. Our study further suggests that aerosol-sized PM may be generated even in healthy subjects, without coughing or increased sputum, because of airway shear stress, vibration, and sporadic collapse/reopening of terminal bronchioles.…”
Section: Limitationsmentioning
confidence: 73%
“…1,2 There have been heightened safety concerns during the SARS-CoV-2 pandemic 3 , as HCWs are among the highest risk groups for both acquisition of SARS-CoV-2 and severe coronavirus disease 2019 (COVID-19). 4 In general, viruses can be passed from person to person in 3 ways:…”
Section: Introductionmentioning
confidence: 99%
“…The next test found that using only headings from lower in the hierarchy ("Severe acute respiratory syndrome coronavirus 2" or "Coronavirus disease 2019") reduced results by 204, of which 22 were relevant to COVID-19 and one to NICE. The one relevant reference that NICE would miss (Cournoyer et al, 2021) discussed respiratory viruses in general (e.g. influenza) and had been indexed with the Emtree heading for SARS-CoV-1.…”
Section: Refinements To Create the Recommended Strategymentioning
confidence: 99%
“…The final strategy is presented in Figure 4 with limits applied (Table 12). This increase in specificity from Strategy A has been achieved with the loss of only one reference of minimal relevance to NICE that does not directly refer to COVID-19 (Cournoyer et al, 2021).…”
Section: Simplifying the Refined Strategy Cmentioning
confidence: 99%
“…If the patient arrives via emergency medical service and the patient is being ventilated via a bag-valve-mask, ventilations should be paused as the patient is transported from the ambulance bay to the designated ED area as this is an AGP. 23 Once in a controlled environment, if there is a prehospital airway, placement should be confirmed and secured by those in modified droplet and airborne precautions PPE, a viral filter placed or confirmed, and a mechanical CPR device attached if available and not already present. An attempt to exchange a prehospital supraglottic airway to an endotracheal tube (ETT) when the prehospital device is functional is not recommended given the risk of aerosolization.…”
Section: Decrease the Number Of Agpsmentioning
confidence: 99%